2018
DOI: 10.3126/ijosh.v1i1.13812
|View full text |Cite
|
Sign up to set email alerts
|

The effects of leadership on safety outcomes: The mediating roles of trust and safety climate

Abstract: Abstract:Background: In the current study, the mediating roles of safety climate and trust in the relations between leadership styles which are transformational and transactional and safety outcomes which are safety compliance and safety participation are studied. Methods and Material: 101 blue-collar workers from a company in Zonguldak were participated in the study. Results: The results showed that transactional leadership is strongly associated with safety climate. As predicted, transformational leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This result is supported by the literature showing that transformational leadership positively contributes to safe behaviours [44,55,56]. In addition, transformational leadership is the proven means of creating a safety climate in the organization, positively affecting employees' perceptions of the workplace safety climate [13,25,27,[48][49][50][51].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…This result is supported by the literature showing that transformational leadership positively contributes to safe behaviours [44,55,56]. In addition, transformational leadership is the proven means of creating a safety climate in the organization, positively affecting employees' perceptions of the workplace safety climate [13,25,27,[48][49][50][51].…”
Section: Discussionmentioning
confidence: 54%
“…One of the key factors influencing the safe behavior of employees is safety leadership. Studies show that transformational leadership in safety leadership has a positive effect on the safe behavior of employees [25,59]. For example, Mullen et al [47] found in their study that transformational leadership has a positive effect on both dimensions (safety compliance and safety participation) of employees' safe behavior in young and adult participants.…”
Section: Transformational Safety Leadership and Safe Behaviormentioning
confidence: 98%
See 2 more Smart Citations
“…This study’s primary theoretical contribution lies in its novel integration of the LMX and SRF theories to yield a nuanced picture of the relationship between transformational leadership and safety compliance in workplace safety management. Studies on safety compliance have long observed the positive effects of transformational leadership, which fosters employees’ intrinsic motivations [ 60 ], feelings of trust [ 61 ], and greater sensitivity to job-related characteristics [ 62 ]. Previous studies have also suggested a negative or non-significant effect of transformational leadership on safety compliance [ 7 , 19 ].…”
Section: Discussionmentioning
confidence: 99%